2006
DOI: 10.1038/modpathol.3800621
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 protein overexpression and CCND1 amplification in breast carcinomas: an immunohistochemical and chromogenic in situ hybridisation analysis

Abstract: Conflicting results on the prevalence of cyclin D1 ovexpression and its correlation with CCND1 amplification and outcome of breast cancer patients have been reported. Owing to limited sensitivity and specificity of most antibodies against cyclin D1, evaluation of cyclin D1 immunoexpression is reported to be problematic. The aims of this study were to assess the prevalence of cyclin D1 expression in breast carcinomas using the SP4 rabbit monoclonal antibody; to correlate cyclin D1 expression with amplification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
146
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 45 publications
(116 reference statements)
17
146
2
Order By: Relevance
“…The majority of basal-like breast cancers lack or show low levels of ER and PR, lack HER2 protein overexpression and HER2 gene amplification, whereas they express genes and proteins usually found in 'basal'/myoepithelial cells of the normal breast including high-molecular-weight cytokeratins (5/6, 14 and 17), 17,19,21,42 P-cadherin, 43 caveolins 1 and 2, 44,45 nestin, 46 aB crystallin, 47,48 CD109, 49,50 and EGFR 17 and, in a minority of cases, harbor EGFR gene amplification 51 or aneusomy. 52 p53 immunohistochemical expression or TP53 gene mutations is observed in up to 85% of cases, 53,54 and alterations of the pRB and p16 G1/S cell-cycle checkpoint are remarkably prevalent in these cancers. 33,55 A recent study demonstrated that approximately 30% of basal-like breast cancers concurrently show lack of pRB expression, overexpression of p16 and p53 immunoreactivity (pRBÀ/p16 þ /p53 þ ), whereas this profile was rarely seen in tumors of other molecular subtypes.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of basal-like breast cancers lack or show low levels of ER and PR, lack HER2 protein overexpression and HER2 gene amplification, whereas they express genes and proteins usually found in 'basal'/myoepithelial cells of the normal breast including high-molecular-weight cytokeratins (5/6, 14 and 17), 17,19,21,42 P-cadherin, 43 caveolins 1 and 2, 44,45 nestin, 46 aB crystallin, 47,48 CD109, 49,50 and EGFR 17 and, in a minority of cases, harbor EGFR gene amplification 51 or aneusomy. 52 p53 immunohistochemical expression or TP53 gene mutations is observed in up to 85% of cases, 53,54 and alterations of the pRB and p16 G1/S cell-cycle checkpoint are remarkably prevalent in these cancers. 33,55 A recent study demonstrated that approximately 30% of basal-like breast cancers concurrently show lack of pRB expression, overexpression of p16 and p53 immunoreactivity (pRBÀ/p16 þ /p53 þ ), whereas this profile was rarely seen in tumors of other molecular subtypes.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…82,83 The majority of tumors arising in BRCA1 germ-line mutation carriers, in particular those diagnosed before 50 years of age, have morphological features similar to those described in basal-like cancers 84,85 and show a basal-like phenotype as defined by immunohistochemistry 86,87 or expression arrays. 8 Both basal-like breast cancers and tumors arising in BRCA1 germ-line mutation carriers show a peculiar pattern of cell-cycle protein expression; 54,84,88,89 both rarely harbor CCND1 gene amplification; 54,88 however, they express significantly lower levels of p27, 84,89 and higher levels of Skp2, 84,89 cyclin E, 84,89 and caspase-3, 89 when compared with sporadic breast carcinomas and BRCA2 mutation tumors.…”
Section: S Badve Et Almentioning
confidence: 99%
“…BACs were digoxigenin labelled as previously described [42]. In addition, chromogenic in situ hybridisation (CISH) with probes for CCND1, MYC, HER2 and TOP2A was performed as previously described [9,15,42]. The CCND1 probe maps to the smallest region of amplification on 11q13 as previously defined by high resolution microarray-based comparative genomic hybridisation analysis [6,[27][28][29][30].…”
Section: Chromogenic In Situ Hybridisationmentioning
confidence: 99%
“…CTTN has been shown to play a critical role in various actin-mediated processes such as cell migration, adhesion and receptor mediated endocytosis [2,4]. 11q13 amplification is found in up to 15% of breast cancers [5][6][7][8] and has been suggested to be associated with oestrogen receptor (ER)-positive disease [9][10][11], lobular histological type [11,12], and poor prognosis [11,[13][14][15][16]. The 11q13 amplicon is complex and encompasses multiple cores [6,8,14,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation